Kaji Eksperimental Variasi Diameter Turbin Angin Propler Terhadap Performa Turbin Angin Hybrid - Fadel Firanda; Iwan Kurniawan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In this research carried out innovation in wind turbine that generate power using wind energy. Where two different wind turbines are combined into a hybrid wind turbine. There are conventional wind turbine (propeller) and wind ball energy (venturi). Both types of wind turbines are still in the same axis of the shaft. This research is done with the intention that this hybrid wind turbine can work well at low wind speeds. This study was conducted to determine the addition of wind turbine propeller performance after the merger with wind ball energy. The hybrid wind turbine performance is measured on each diameter variation of propeller wind turbine’s blade. So we get the right ratio between the diameter of the propeller wind turbine and wind ball energy in this hybrid. In this study using three variations of wind turbine propeller diameter, there are 160 cm, 200 cm and 240 cm with 3 pieces of blade on each variation. Propeller’s blade profile using NREL S833. Wind ball energy were later added in front of propeller turbine. Number of wind ball energy’s blade is 5 pieces with a diameter of 0.5 meters. From the test results known that with the addition of a wind ball energy on a propeller wind turbine with smallest diameter has the greatest percentage increase in performance among the three variations of wind turbine propeller diameter. Key word: wind ball energy, wind turbine, hybrid